2017
DOI: 10.1371/journal.pone.0172426
|View full text |Cite
|
Sign up to set email alerts
|

Human cortical neural correlates of visual fatigue during binocular depth perception: An fNIRS study

Abstract: Functional near-infrared spectroscopy (fNIRS) was adopted to investigate the cortical neural correlates of visual fatigue during binocular depth perception for different disparities (from 0.1° to 1.5°). By using a slow event-related paradigm, the oxyhaemoglobin (HbO) responses to fused binocular stimuli presented by the random-dot stereogram (RDS) were recorded over the whole visual dorsal area. To extract from an HbO curve the characteristics that are correlated with subjective experiences of stereopsis and v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 43 publications
1
16
0
Order By: Relevance
“…The initial in vitro results and a previous report also supported these clinical results. In a previous report, neural activity correlated with eye fatigue [ 49 ]. In our previous work, our group revealed that orally provided L. paracasei KW3110 interacted with the gut immune cells in mice and oral administration of L. paracasei KW3110 enhanced the cytokine levels in blood [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The initial in vitro results and a previous report also supported these clinical results. In a previous report, neural activity correlated with eye fatigue [ 49 ]. In our previous work, our group revealed that orally provided L. paracasei KW3110 interacted with the gut immune cells in mice and oral administration of L. paracasei KW3110 enhanced the cytokine levels in blood [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The GLM analysis was performed as follows: for each participant, the hemodynamic response function (HRF) filter and a wavelet-minimum description length (MDL) detrending algorithm were used to remove physical noise and artifacts, and a baseline correction was performed. After the wavelet-MDL-based detrending, the average HbO time series were estimated by integrating each HRF with the relevant experimental paradigms ( Cai et al, 2017 ). In the current study, GLM can describe a measurement of change in HbO in terms of a linear combination of two conditions (swab contact and acupuncture) and two groups (medical professional and non-medical professional).…”
Section: Methodsmentioning
confidence: 99%
“…Visual fatigue, a condition of improper or reduced visual function is believed to result from the use or overuse of the eyes and has attracted and puzzled researchers from many different fields ( Franco and Franco , 2001 ; Cai et al, 2017 ). A sense of eye strain, eye weakness, or eye fatigue (i.e., asthenopia, Hofstetter et al, 2000 ), in combination with musculoskeletal symptoms from the neck and shoulder region, has been widely acknowledged as being associated with occupational near work since the 1980s ( Gobba et al, 1988 ; Piccoli and ICOH Scientific Committee, 2003 ; Blehm et al, 2005 ).…”
Section: Introductionmentioning
confidence: 99%